Pierre Aubenque. Problèmes Aristotéliciens –II– Philosophie Pratique, Paris, Librairie Philosophique J. Vrin, 2011, 264 pp. - Massini Correas, Carlos I. (2012)
Fil: Massini Correas, Carlos I.. Universidad de Mendoza